Soil Air Composition and Groundwater Level in a Cultivated Peatland Underlain by Black Schist - Mäkelä, Minna; Simojoki, Asko; Kanerva, Sanna; Yli‐Halla, Markku (European journal of soil science, 2025)
ABSTRACT The effect of field hydrology on microbial gas production in a black schist‐based acid sulfate soil was investigated to find out if conditions in the field are conducive to greenhouse gas formation and to see if the overlying peat functions as protection against oxidation of the sulfidic material. Soil air composition and hydrological conditions were observed in an agricultural peatland, which contains black schists and acid sulfate soil properties beneath a layer of peat 15–60 cm thick at different observation sites. The field was drained with open ditches with 20 m spacing. Groundwater level was high, particularly at low elevations of the field, and the acid sulfate subsoil was at or near saturation for much of the investigated period (15 months). Within the soil profile, CO2 concentration increased and O2 concentration decreased with increasing depth, indicating microbial activity, while the variation of N2O content within the profile was not as clear. The acid sulfate subsoil was predominantly saturated with water and consequently had slow gas exchange and only modest microbial activity. These results explain previous results of unexpectedly low greenhouse gas emissions from this location. They also suggest that a thick peat layer may protect against the oxidation of underlying sulfidic horizons, even if the extent of protection remained inconclusive.